2000
DOI: 10.1037/1076-8971.6.4.1098
|View full text |Cite
|
Sign up to set email alerts
|

The science of infanticide and mental illness.

Abstract: Women who murder their children have been the subject of intensive media and public scrutiny. Reactions have varied from horror at the cruelty of the act to sympathy for the perpetrator, based on the belief that the mother must have been severely mentally disordered or at least suffering from a diminished mental capacity at the time of the offense. As a result, the English and American legal systems have adopted very different legal responses to this crime. Underlying these legal positions are assumptions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 43 publications
5
52
0
1
Order By: Relevance
“…The U.S. legal system has treated maternal filicide as murder regardless of the mental health status of the mother. By contrast, postpartum psychosis is a mitigating factor in Britain, where women are considered to be susceptible to depressive symptoms within the 1st year of childbirth (Dobson & Sales, 2000). Other countries, including Canada, Australia, Austria, Germany, and New Zealand, have adopted similar approaches to maternal filicide (Dobson & Sales, 2000).…”
Section: Postpartum Psychosis: a Valid Defense?mentioning
confidence: 93%
“…The U.S. legal system has treated maternal filicide as murder regardless of the mental health status of the mother. By contrast, postpartum psychosis is a mitigating factor in Britain, where women are considered to be susceptible to depressive symptoms within the 1st year of childbirth (Dobson & Sales, 2000). Other countries, including Canada, Australia, Austria, Germany, and New Zealand, have adopted similar approaches to maternal filicide (Dobson & Sales, 2000).…”
Section: Postpartum Psychosis: a Valid Defense?mentioning
confidence: 93%
“…This has surely contributed to difficulties in introducing them for defence purposes. Dobson and Sales (2000), for example, contend that while there is a specific link between childbirth and post-partum 'blues', as evidenced by its frequency, and because post-partum blues occur at a very specific time (three to eight days) following childbirth, this mental disturbance is unlikely to be causative with respect to either neonaticide or filicide, because its onset is typically too late to affect those committing neonaticide and too brief to play a major role in filicide. They do not distinguish between post-partum depression and other 370 R. Langer clinical depression, referring to the standard clinical and research diagnostic criteria described in the DSM (without reference to Axis IV issues such as psychosocial context), as characterized by 'dysphoric mood, loss of interest in usually pleasurable activities, loss of appetite, sleep disturbance, fatigue, difficulties in making decisions, excessive guilt, and suicidal thoughts' (Dobson andSales 2000: 1105).…”
Section: Problems In Defining Post-partummentioning
confidence: 95%
“…Dobson and Sales (2000), for example, contend that while there is a specific link between childbirth and post-partum 'blues', as evidenced by its frequency, and because post-partum blues occur at a very specific time (three to eight days) following childbirth, this mental disturbance is unlikely to be causative with respect to either neonaticide or filicide, because its onset is typically too late to affect those committing neonaticide and too brief to play a major role in filicide. They do not distinguish between post-partum depression and other 370 R. Langer clinical depression, referring to the standard clinical and research diagnostic criteria described in the DSM (without reference to Axis IV issues such as psychosocial context), as characterized by 'dysphoric mood, loss of interest in usually pleasurable activities, loss of appetite, sleep disturbance, fatigue, difficulties in making decisions, excessive guilt, and suicidal thoughts' (Dobson andSales 2000: 1105). Thus, by failing to identify childbirth and new motherhood as a significant life event requiring major adjustments in primary social relationships, and potentially problematic changes to employment status, housing, and access to health and other social services, they are able to conclude that 'in contrast to post-partum blues, which appear to be a direct consequence of childbirth, there is little convincing evidence that post-partum depression differs from depression occurring at other times in a woman's life' (Dobson andSales 2000: 1105).…”
Section: Problems In Defining Post-partummentioning
confidence: 95%
See 1 more Smart Citation
“…It is suggested that these may be symptoms of pre-existing mental illness, which may be worsened by tiredness, changes in schedule, and stress resulting from the parenting role [14].…”
Section: Introductionmentioning
confidence: 99%